PRILAKU ORGANISASI DAN KEPEMIMPINAN PENDIDIKAN ISLAM - Atnawi Atnawi; Abdul Munib; Abd Haris (Journal of Education Partner, 2023)
Organizational behavior and leadership play a crucial role in creating an effective educational environment, especially in the context of Islamic education in educational institutions. Islamic education not only aims to transfer religious knowledge but also to shape character and morality by Islamic teachings. Good organizational behavior in an educational environment includes various aspects, such as effective communication, fairness, participation, and managerial support. Positive organizational behavior creates a harmonious and productive work atmosphere, enabling teachers and administrative staff to work collaboratively to achieve educational goals. Meanwhile, leadership in the context of Islamic education requires leaders who not only have strong managerial skills, but also understand Islamic values ​​and can integrate them into their leadership practices. The research method used in this research activity is a library approach. The steps taken in this research are 1) identification of research objectives, 2) selection of library sources, 3) search strategy for information sources, 4) selection of literature, 5) analysis of literature related to data, 6) synthesis of research findings. Meanwhile, research findings include that Islamic educational leadership must inspire, guide and motivate staff and students to achieve academic and spiritual success. However, in some contexts, poor organizational behavior or ineffective leadership can hinder the achievement of Islamic education goals. For example, a lack of effective communication can lead to ambiguity in the implementation of Islamic education programs, while a lack of fairness can create dissatisfaction among staff and students. Therefore, research on the relationship between organizational behavior and Islamic educational leadership is very important to understand how these factors influence each other in creating an educational environment that is effective and oriented towards Islamic values. With a better understanding of this relationship, Islamic educational institutions can develop more effective management strategies and practices to improve the quality of education and achieve their Islamic educational goals.